Class III malocclusion with severe anteroposterior discrepancy - Susana Maria Deon Rizzatto (Dental Press Editora, 2012)
This study aims at reporting the clinical case of a patient with Class III skeletal malocclusion with severe maxillary deficiency, producing a reduced midface associated with severe mandibular prognathism. The pre-surgical orthodontic preparation was composed mainly by dentoalveolar expansion and repositioning of the incisors in the lower arch. Then, a combined maxillary and mandibular orthognathic surgery was performed. The treatment objectives were achieved, with significant improvement in facial esthetics and occlusion, followed by post-treatment stability. This case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO), as part of the requirements for obtaining the title of Diplomate by BBO. O objetivo deste artigo é relatar o caso clínico de um paciente portador de má oclusão de Classe III esquelética com acentuada deficiência maxilar, causando redução do terço médio da face, associada a severo prognatismo mandibular. O preparo ortodôntico pré-cirúrgico foi composto, principalmente, pela expansão dentoalveolar da maxila e o reposicionamento dos incisivos na arcada inferior. Depois, foi realizada a cirurgia ortognática combinada maxilomandibular. Os objetivos do tratamento foram atingidos, com significativa melhora da oclusão e da estética facial, seguida de estabilidade pós-tratamento. Esse caso foi apresentado à Diretoria do Board Brasileiro de Ortodontia e Ortopedia Facial (BBO), como parte dos requisitos para obtenção do título de Diplomado pelo BBO.